Dichlorido{4-cyclohexyl-1-[1-(2-pyridyl-kappa N)ethylidene]thiosemicarbazidato-kappa N-2(1),S}phenyltin(IV) - Salam, M.A.; Abu Affan, M.; Ahmad, F.B.; Tahir, M.I.M.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The Sn-IV atom in the title compound, [Sn(C6H5)(C14H19-N4S) Cl-2], exists within a distorted octahedral geometry defined by the N, N', S-tridentate monodeprotonated Schiff base ligand, two mutually trans Cl atoms, and the ipso-C atom of the Sn-bound phenyl group; the latter is trans to the azo-N atom. The greatest distortion from the ideal geometry is found in the nominally trans angle formed by the S and pyridyl-N atoms at Sn [151.03 (4)degrees]. With the exception of the cyclohexyl group (chair form), the Schiff base ligand is almost planar (r.m.s. deviation of non-H and Sn atoms = 0.053 angstrom). The nearly orthogonal orientation of the Sn-bound phenyl group [N-Sn-C-C torsion angle = 70.8 (5)degrees] to the planar portion of the Schiff base allows for the formation of significant intramolecular C-H center dot center dot center dot Cl interactions which preclude the Cl atoms from participating in N-H center dot center dot center dot Cl hydrogen bonds. Instead, C-H center dot center dot center dot pi contacts, involving methylene H and the Sn-bound phenyl group, lead to the formation of supramolecular chains that pack in the bc plane. Connections between these layers are of the type C-H center dot center dot center dot Cl.